Crystallizing Galactocele: A report of an unusual case - Katoch, Nandita; Kanupriya, Kanupriya; Verma, Nikhil (Indian Journal of Case Reports, 2025)
Galactocele is a benign cystic lesion of the breast and is commonly seen in pregnancy and lactation. Crystals in galactocele are rarely seen and reported. Crystals form due to supersaturation of milk with solutes and obstruction of the draining ducts. Fine needle aspiration cytology is used for a dual purpose, i.e., diagnostic and therapeutic procedure in such cases. Here, we present the case of crystallizing galactocele in a 27-year-old female.